2016
DOI: 10.1080/13504622.2016.1233389
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating place-based environmental education through bird studies: an action research investigation

Abstract: This study involved a workshop designed to support biology teachers in conducting birdwatching activities with their students and to promote place-based environmental education in Turkey. The instruments for collecting data were a workshop questionnaire and interviews. The findings revealed that initial response to the workshop was positive; participating teachers reported that the resources and strategies motivated them to conduct bird studies with students. They identified barriers and noted that the place-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(34 reference statements)
1
4
0
1
Order By: Relevance
“…The location area factor that influences the richness of bird species in the study location is the same as that found by Lazarina et al (2020), Callaghan et al (2018), Fadrikal et al (2015, and Reis et al (2012). Locations with broader areas tended to have a higher bird species richness as well.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The location area factor that influences the richness of bird species in the study location is the same as that found by Lazarina et al (2020), Callaghan et al (2018), Fadrikal et al (2015, and Reis et al (2012). Locations with broader areas tended to have a higher bird species richness as well.…”
Section: Discussionsupporting
confidence: 56%
“…Exposure to noise was the most limiting factor for this bird community in the urban landscape (Pena et al 2017). Open space is the remaining habitat in the urban landscape; thus, the presence of green open space in urban areas can reduce the loss of bird diversity in urban landscapes (Callaghan et al 2018) and have a positive effect on bird diversity (Rodrigues et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study presented here focuses on the implementation of an EE program which used the topic of ornithology (Can et al, 2017) to introduce children from a rural community to the world of the scientific observation of birds, and through this to the importance of maintaining the biodiversity of birds in nature. Therefore, the aim of the study was to investigate the influence of an EE program (named the Lesser Kestrel program) on the development of elementary school students' system thinking skills in the context of bird ecology.…”
Section: Introductionmentioning
confidence: 99%